Mucosal microbiome of surgically treated terminal ileal Crohn’s disease - Loch, Florian N.; Kamphues, Carsten; Menzel, Peter; Schwarzer, Rolf; Beyer, Katharina; Schineis, Christian (Frontiers in Cellular and Infection Microbiology, 2024)
Crohn’s disease (CD) is associated with changes in the microbiome. The role of these changes and their precise association with disease course and activity remain ambiguous. In this prospective single-center study, the mucosal microbiome of surgical CD and non-CD patients was compared at the time of surgery. Microbial analyses were individually performed for ileal and colonic tissue samples obtained during surgery using 16S-rRNA-gene amplicon sequencing. Three groups out of the 46 included patients were formed: 1) a study group of CD of patients who received ileocecal resection due to CD involvement (CD study, n=10); 2) a control group of non-CD of patients who received intestinal resection due to indications other than CD (non-CD control, n=27); and 3) a second control group of CD who underwent resection of the intestine not affected by CD (CD non-affected control, n=9). Species richness and Shannon diversity were not different between all formed groups and regions analyzed (p>0.05). Several significant taxonomic differences were seen at the phylum-, order-, and genus-levels between the formed groups, such as a decrease of Firmicutes (phylum-level) and an increase of Bacteroides and Escherichia/Shigella/Pseudescherichia (genus-level) in CD study – colon vs. the non-CD control – colon (p ≤ 0.05). The CD non-affected control presented the largest amount of differentially abundant taxa in comparison to the other groups. These results underline that CD is accompanied by changes in affected and non-affected intestinal regions compared to non-CD controls. This study contributes the mucosal microbiome of a well-defined subset of surgical CD patients without confounding aspects of the fecal microbiome or regional microbial differences to the existing literature.